Low Amplitude Adiabatic Non-radial Stellar Oscillations - Benvenuto, Omar Gustavo (2019)
We present the problem of low amplitude, adiabatic non-radial oscillations starting from first principles. We describe the perturbations imposed to the models, assuming that its non-perturbed structure is spherical. Then, we restrict ourselves to the case of adiabatic oscillations, presenting the equations written in terms of the Dziem- bowski variables. We describe a numerical method for solving these equations based on finite differences and apply it for the simple case of polytropic spheres. A computer code based on this algorithm is available at the web page of the school. This method can be easily generalised for computing the case of low amplitude, non-adiabatic, non-radial pulsations.